Thermal Stability and Decomposition Mechanism of Poly(alkylene succinate)s - Rizos D. Bikiaris; Nina Maria Ainali; Evi Christodoulou; Nikolaos Nikolaidis; Dimitra A. Lambropoulou; George Z. Papageorgiou (Macromol, 2022)
In the present study, a series of aliphatic polyesters based on succinic acid and several diols with 2, 4, 6, 8, and 10 methylene groups, namely poly(ethylene succinate) (PESu), poly(butylene succinate) (PBSu), poly(hexylene succinate) (PHSu), poly(octylene succinate) (POSu), and poly(decylene succinate) (PDeSu), were prepared via a two-stage melt polycondensation method. All polyesters were semicrystalline materials with Tm ranging from 64.2 to 117.8 °C, while their Tg values were progressively decreasing by increasing the methylene group number in the used diols. Thermogravimetric analysis (TGA) revealed that the synthesized poly(alkylene succinate)s present high thermal stability with maximum decomposition rates at temperatures 420–430 °C. The thermal decomposition mechanism was also evaluated with the aid of Pyrolysis–Gas chromatography/Mass spectrometry (Py–GC/MS), proving that all the studied polyesters decompose via a similar pathway, with degradation taking place mainly via β–hydrogen bond scission and less extensive with homolytic scission.